Laju Infeksi Ganoderma pada Empat Kelas Tekstur Tanah - Agus Susanto; Agus Eko Prasetyo; Sri Wening (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
Basal stem rot disease caused by Ganoderma is the most destructive disease in oil palm plantation in Indonesia. Development of this disease is faster and heavier in nutrient poor soils, such as sandy soil. The objective of this research is to study and quantitatively measure the infection rate of Ganoderma disease in sandy soil. The treatments consisted of five different mixtures of mineral soil (M) and sand (P) i.e: A (100% M–0% P), B (75% M-25% P), C (50% M-50% P), D (25% M-75% P), and E (0% M-100% P). Physical, chemical, and biological properties of each soil mixture treatment were analyzed. Soil texture can be differentiated into sandy clay loam, sandy loam, loamy sand, sand for treatmen A, B, C, D, E, respectively. Sandy soil medium had less microorganism population (< 1 × 106 cfu g-1soil) than sandy clay loam which microrganism population was 3 × 106 cfu g-1 soil. The infection rate of Ganoderma in sandy soils was 1.77–1.83 palm per month per 100 palms. Infection rate of Ganoderma in sandy soil was faster and higher than those in loamy soilKey words: basal stem rot, oil plam, sandy soil